Single source precursor driven phase selective synthesis of Au–CuGaS2 heteronanostructures: an observation of plasmon enhanced photocurrent efficiency. Issue 4 (20th December 2017) - Ghosh, Abhisek Brata; Saha, Namrata; Sarkar, Arpita; Dutta, Amit Kumar; Satra, Jit; Adhikary, Bibhutosh
Abstract : Coupling of metallic Au with CuGaS2, synthesized from single molecule precursor [Ga(acda)3 Cu(PPh3 )2 ]NO3, results Au–CuGaS2 heterostructure which shows remarkably high photocurrent response compared to CuGaS2 . Abstract : The design of new functional metal–semiconductor heteronanostructures with improved photovoltaic efficiencies has drawn significant attention because of their unprecedented properties and potential applications. Herein, we report a phase selective synthesis of ternary CuGaS2 (wurtzite and tetragonal) by simple solution based thermal decomposition of a new binuclear single molecular precursor [Ga(acda)3 Cu(PPh3 )2 ]NO3 (acda = 2-aminocyclopentene-1-dithiocarboxylic acid, PPh3 = triphenylphosphine) where the phase selectivity has been achieved easily by changing the combination of surface active agents. Furthermore, we have extended our approach to develop a well-controlled synthetic strategy for the preparation of a Au–CuGaS2 heteronanocomposite with both the phases. A detailed microscopic study reveals that during heterostructure synthesis, an epitaxial junction has been formed at the interface of ternary CuGaS2 and metallic Au. To find out the influence of this epitaxial connectivity on the properties, we have studied the photocurrent and photoresponse behavior of the material and compared them with that of bare CuGaS2 . For both the wurtzite and tetragonal phases, the Au–CuGaS2 twin structure exhibits a plasmon enhanced superior charge transport ability and an abruptly high photocurrent density compared to that of pure CuGaS2 . Due to efficient charge separation by strong plasmon–exciton coupling at the interface, Au–CuGaS2 can be used as a potential candidate for photoelectrochemical applications.